2006
DOI: 10.1038/sj.ki.5000344
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal calcium and magnesium transporter abundance in streptozotocin-induced diabetes mellitus

Abstract: Diabetes is associated with renal calcium and magnesium wasting, but the molecular mechanisms of these defects are unknown. We measured renal calcium and magnesium handling and investigated the effects of diabetes on calcium and magnesium transporters in the thick ascending limb and distal convoluted tubule in streptozotocin (STZ)-induced diabetic rats. Rats were killed 2 weeks after inducing diabetes, gene expression of calcium and magnesium transporters in the kidney was determined by real-time polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 38 publications
5
49
1
2
Order By: Relevance
“…However, these differences may be explained by the dietary Mg 2+ intake of the subjects, since patients in the original study showed reduced Mg 2+ intake (,250 mg/day) (71). The mRNA expression of TRPM6 is changed in diabetic rats, although results are contradictory and may depend on the experimental model used (96,97). Whereas some report increased TRPM6 expression (96), others show that TRPM6 is downregulated (97).…”
Section: Trpm6mentioning
confidence: 95%
“…However, these differences may be explained by the dietary Mg 2+ intake of the subjects, since patients in the original study showed reduced Mg 2+ intake (,250 mg/day) (71). The mRNA expression of TRPM6 is changed in diabetic rats, although results are contradictory and may depend on the experimental model used (96,97). Whereas some report increased TRPM6 expression (96), others show that TRPM6 is downregulated (97).…”
Section: Trpm6mentioning
confidence: 95%
“…Because insulin has been implicated in enhancing Mg reabsorption at the TAL, insulin deficiency or resistance in the diabetic state can promote Mg wasting at this nephron segment (58). The expression of paracellin 1 in TAL, however, has not been shown to be increased in diabetic rats (66).…”
Section: Renal Causesmentioning
confidence: 99%
“…Similarly, rats with experimentally induced diabetes display a significant increase in the fractional excretion of Ca 2+ [41]. However, these diabetic rats showed increased mRNA and protein levels of both TRPV5 and calbindin-D 28K .…”
Section: Clinical Relevancementioning
confidence: 99%